UMA NARRATIVA MIDIATIZADA DO COTIDIANO: As charges de Política Internacional de Angeli (2001-2012) - Barros, Iberê Moreno Rosário e (2015)
This research is part of the discussion about midiatic communication in social interactions. Has as a theme, the cartoon as a midiatic narrative of the everyday. From a literature analysis and the an practical exercise, in which we studied the collection O lixo da história, published by Companhia das Letras. Among the authors and theories used, we highlight: the narrative concept, of Luiz Gonzaga Motta; the midiatization idea from José Luiz Braga studies; the cultural mediation theory from Jesús Martin-Barbero; the everyday studies of Michel de Certeau; and the understanding of culture, based upon Cultural Studies. The readings and analysis showed us the perspectives that the cartoon is an absurd narrative and a narrative of the absurd of a historic moment, in a way that it becomes a historiographic monument of the everyday. Like its done with tha journalistic narrative, the cartoon demands a critic vision, looking for more than its shape, but all the surroundings.